Síndrome de Burnout y factores sociodemográficos-organizativos en profesionales de salud. Hospitales del callejón de Conchucos, Ancash, Perú - 2012 - Yslado M., Rosario (2013)
We aimed to identify, demographic and organizational factors related to Burnout Syndrome in health care at hospitals and clinics, located in Huari, Pomabamba and Sihuas, Ancash, Peru. We evaluated 76 health care professionals, ages 20-59, both sexes, including physicians, registered nurses, midwives, dentists, psychologists, pharmacists, who completed the questionnaire “Burnout Syndrome in health care professionals of DIRES Ancash. 2012” and Maslach Burnout Inventory - MBI (1997). We found that 57.9% of health care professionals had early stage Burnout Syndrome, 14.5% had intermediate stage and 27.6%, had final stage (high level of chronic job stress). There was a significant difference between the percentages of the initial and final stage (p<0.05). There was a statistically significant relationship (p<0.05) between sociodemographic (lack of home owner-ship) and organizational factors, such as (contradictory orders from the boss; lack of, emotional and instrumental support among co-workers; and limited recreational activities, vacation time and days off, with the final stage of Burnout Syndrome. This study partially confirmed the general and the specific hypotheses.